Problematic issues of using the toolkit of economic cybernetics - V. Persianov; A. Kurbatova (Управление)
Arange of issues, related to the use of cybernetics in economic research, technological development and educational programs for training specialists of management, has been considered. A large contribution of this science to the space exploration, designing counting machines, etc., – has been noticed. At the same time, focusing on management in systems, it did not pay enough attention to many important functions and specifics of socio-economic processes. Cybernetics tried to change some traditional ideas about the possibilities and methods of goal-setting in management of economic processes in the centrally planned Soviet economy, but these attempts were ineffective. More so, cybernetics was unable to affect the spiritual and moral sphere of human life and society, the content and development of such sciences as philosophy, sociology, political economy, etc.It has been shown, that the tendency to revise the fundamental provisions of the Humanities can lead and often leads to false conclusions, believing, that the qualitative differences between the system objects are insignificant. Agreeing, that setting limits to the possibilities of computer modeling in advance is impossible, it must be recognized, that the machines created by cybernetics, remain only an objectification – a “truncated” (incomplete) form of any kind of human activity, including management (purposing, selection of criteria, decision-making, etc.).The goal setting requires at least a normal human intelligence. At the same time, “individual survival” is not the main universal task: in natural selection, the survival of the species is often achieved by the death of a significant part of specimens.The article pays considerable attention to the cybernetic approach to the study of socio-economic processes. It is noted, that the thesis about cybernetically expedient functioning of any social systems (this point of view is shared by some specialists in cybernetics) contradicts common sense. Capitalism would have to be seen as a planned system, alien to the anarchy of production, and in fact as a system, which solves pre-set tasks corresponding to the interests of society. Therefore, according to the authors, the concept of self-governing system in the cybernetic sense is not applicable to a society with a market economy.